PENYELENGGARAAN PENDIDIKAN PERSPEKTIF GENDER - M. Jamaluddin; Ubabuddin (ENTINAS: Jurnal Pendidikan dan Teknologi Pembelajaran, 2026)
Gender-sensitive education is the process of implementing strategies to internalise gender-sensitive values among learners through an interdisciplinary approach, with the aim of fostering gender awareness and justice. Justice and equality are the fundamental concepts underpinning the primary goals and mission of human civilisation to achieve well-being, foster harmony in community and national life, and build high-quality families. Gender equality refers to the equal conditions for men and women to access opportunities and their rights as human beings, enabling them to play a role and participate in political, legal, economic, socio-cultural, educational, and national defence and security activities. The process of delivering education from a gender perspective involves fostering gender awareness and justice through the concepts and application of equal participation, access, control and benefits for every learner, grounded in the Qur’an and legislation on gender and gender justice, with a focus on preparing a generation that excels and finds happiness in both this world and the hereafter.